A conceptual cooperative model designed for processes, digitalisation and innovation. Issue 4 (9th December 2019) - Sehlin, Daniel; Truedsson, Maja; Cronemyr, Peter
Abstract : Purpose: Digital transformations are changing society, and they force industries to react to the market more frequently. Managers are aware of new technical demands, which increase the pressure of meeting those demands. To meet technical demands, radical innovations are one way to stay competitive. However, it is more complex to make them a part of the business. The purpose of this study was to create a framework for small and medium-sized enterprises to become more efficient by starting to digitalise their business processes with the expertise of an external innovation partner. Design/methodology/approach: The study was performed at a case company with an abductive approach where both deduction and induction were used to study the empirical findings and formulate new theories in relation to recognised theory. Qualitative methods have been used in the empirical study due to their flexibility and the fact that the focus of the information gathering was to create a context. Findings: The analysis indicates that a certain level of process maturity can be put in relation to a certain innovation level and a certain level of digital change. According to a process maturity model, an adaptable process could respond to changes in customer demands better, which can be related to changes in the business domain and the society. The research resulted in a conceptual cooperative model based on the three domains of the study. The model has been validated using design reviews with the case company, a consultancy firm and together with an innovation partner. Practical implications: The model will be a practical template for Small and Medium Enterprises to follow when digitalising business processes and how to prioritise them. Originality/value: The proposed framework of how to digitalise at different innovation levels coupled to process maturity levels is a novel idea that could be used for further research.